Needs analysis of thinking style and higher order thinking skills for solving problems in producing products - Yee, Mei Heong; Hamdan, Nuraffefa; Masran, Saiful Hadi; Ibrahim, Badaruddin; Tee, Tze Kiong; Kok, Boon Ching; Azid, Nurulwahida (Penerbit UTHM, 2022)
Problem solving is a practical method that aims to generate ideas to form some more practical and effective solutions. The generation of ideas in the producing products requires complex thinking that is higher order thinking skills (HOTS). The purpose of this study is to analyse the need for thinking style and HOTS to solve problems in producing products among students. The design of this study is descriptive with a quantitative approach. Total numbers of 895 technical students at Sultan Abdul Halim Muadzam Shah Polytechnic were randomly selected as the study sample. A set of questionnaires was developed as the research instrument. Data were then analysed using SPSS software and presented in the form of mean, frequency, and percentage. Studies show that 85.5% of students face problems while solving tasks in the form of problem solving in producing products. The most common problem faced when completing tasks in producing products is finding ideas to develop a product. Factors of difficulties in solving problems for the production of a product are lack of specialized skills, lack of knowledge of specialized skills, and lack of specialized training. As a result, students have difficulty in problem-solving during producing products. However, 89.4% of students think that they need knowledge of thinking style and HOTS that provide a complete description of work steps to solve problems in product production. These findings have implications for students to acquire and improve Thinking Style and HOTS to solve problems in producing products.